Relationship quality and supply chain quality performance: The effect of supply chain integration in hotel industry. (10th July 2020) - Le, Shanghong; Wu, Jinlin; Zhong, Jianlan
Abstract: This study investigates the relationship between relationship quality and supply chain quality performance in hotel supply chain, through the mediating effect of supply chain integration. A questionnaire survey is used to collect data relating to the research hypotheses. Structural equation model technique is suited for our research goals, and the SmartPLS software is implemented to test the conceptual model. The results show that relationship quality has a direct and positive impact on supply chain quality performance; but after introducing mediating variable—supply chain integration, relationship quality indirectly affects supply chain quality performance through supply chain integration. This means that a good relationship quality can promote supply chain integration and ultimately improve supply chain quality performance.